THE ROLE OF MOTIVATION-REGULATION IN MASTER STUDENTS’ ACADEMIC READING - Krismalita Sekar Diasti; Concilianus Laos Mbato (STKIP Persada Khatulistiwa Sintang, 2020)
Abstract: Motivation is a paramount aspect in the learning process. It is a drive that encourages students to achieve better learning results. In the process of accomplishing the learning task, students might encounter difficulties that can demotivate them. Therefore, motivation-regulation is needed to maintain students’ motivation in completing the task. Many studies have been done to investigate master students’ academic reading. Yet, little research has explored master students' motivation-regulation in academic reading. This paper sought to investigate the role of motivation-regulation in master students’ academic reading. It employed mixed-method research where the researchers distributed questionnaires and conducted an interview to collect the data. The research took place at the English Education Master’s Program of Sanata Dharma University from February to April in 2020. There were 14 master students involved in this study. The findings showed that there were three roles of motivation-regulation in master students’ academic reading: (1) Students had high self-efficacy in academic reading which enable them to accomplish the academic reading task; (2) they had an intrinsic interest in academic reading which empowered them to maintain their motivation in the process of academic reading; (3) they had positive emotions towards academic reading. The researchers concluded that the students in this study are capable of regulating their motivation in an academic reading task. This study proposed two suggestions for future research.Keywords: motivation, self-regulated learning, motivation-regulation, academic reading